Nutritional evaluation of Pleurotus florida and Pleurotus sajor-caju harvested spent wheat-rice straw as livestock feed - Kaur, K; Wadhwa, M; Bakshi, M P S; Kapoor, S (The Indian Journal of Animal Sciences, 2012)
A study was undertaken to assess potential use of Pleurotus florida and Pleurotus sajor- caju harvested spent wheat- rice straw as livestock feed. Wheat or rice straw [wheat straw (WS100RS0), wheat-rice straw in 50:50 (WS50RS50), wheat-rice straw in 33:67 (WS33RS67), rice straw (WS0RS100)] were used as substrate for the cultivation of these 2 fungi. The fibrolytic enzyme activity during spawning the substrate was highest in WS50RS50 and WS33RS67. The higher enzyme activity and mushroom yield in these 2 combinations were also responsible for high total ash and CP; low cell wall constituents in these combinations as compared to WS100 or RS100. Irrespective of straw combinations, the florida as compared to P.sajor-caju harvested spent straw had low OM, ADL and cell wall constituents. The net gas production (NGP) and NDF digestibility, irrespective of Pleurotus species was highest and similar in spent WS100 and RS100 and lowest in spent WS33 RS67 straw combination. Irrespective of straw combinations, the P. florida harvested spent straws had highest net gas production, digestibility of NDF and OM as compared to P. sajor-caju harvested spent straw combinations. The effective degradability of DM and NDF in spent straws increased linearly with increase in level of rice straw in spent straw mixture. The rumen fill values of spent straws declined with increase in proportion of rice straw, predicting higher voluntary DM intake of spent straw containing higher proportion of rice straw. The values were highest in spent straw mixture containing 100% rice straw. Irrespective of straw proportion in different combinations, the digestion kinetic parameters for DM and NDF revealed that P. florida as compared to P. sajor-caju spent straw harvested spent straws, had higher degradable fractions (a and b), effective and true degradability and low undegradable fraction and low rumen fill values predicted higher voluntary DM intake. The P. florida harvested spent straw was effectively utilized in ruminant system as compared to P. sajor caju.